Associations of dietary, lifestyle, and other participant characteristics with APC, β-catenin, E-cadherin, and MSH2 expression in the normal mucosa of sporadic colorectal adenoma patients - Shu, Timothy D.; Rutherford, Robin E.; Seabrook, March E.; Barry, Elizabeth L.; Bostick, Roberd M. (Frontiers in Gastroenterology, 2022)
Abnormal expression of Wnt pathway and DNA mismatch repair proteins is common during colorectal carcinogenesis. To investigate cross-sectional associations of lifestyle, dietary, and other participant characteristics with the expression of such proteins, we measured APC, β-catenin, E-cadherin, and MSH2 colorectal crypt expression in biopsies of normal-appearing colorectal mucosa from 104 sporadic colorectal adenoma patients using automated immunohistochemistry and quantitative image analysis. We used multivariable general linear models to compare adjusted mean biomarker expression across categories of participant characteristics. Example findings include that among women relative to men, mean APC expression in whole crypts, the upper 40% of crypts (differentiation zone), and the lower 60% of crypts (proliferation zone) was 322.9% higher (p<0.01), 296.7% higher (p<0.01), and 399.1% higher (p<0.01), respectively. Among participants with higher alcohol consumption, APC expression in the crypt differentiation zone was estimated to be 15.9% lower (p=0.08). Among those with higher total meat consumption, β-catenin expression in whole crypts and the crypt proliferation zone was estimated to be 20.5% higher (p=0.07) and 19.6% higher (p=0.06), respectively, and MSH2 expression in the crypt differentiation zone was estimated to be 64.4% lower (p=0.10). Among those with a higher body mass index, MSH2 expression in the crypt differentiation zone was estimated to be 87.5% lower (p=0.15). These pilot study findings suggest that being male, higher adiposity, and higher alcohol and meat consumption may be unfavorably associated with biomarkers of colorectal carcinogenesis pathway proteins in the normal-appearing colorectal mucosa of sporadic colorectal adenoma patients and support further investigation in larger studies.